2020
DOI: 10.3390/ijerph17103662
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Experience and Psychoeducation Needs When Supporting a Young Person Who Self-Harms

Abstract: Background: Self-harm in young people can have a substantial negative impact on the well-being and functioning of parents and other carers. The “Coping with Self-Harm” booklet was originally developed in the UK as a resource for parents and carers of young people who self-harm, and an adaptation study of this resource was conducted in Australia. This paper presents qualitative analysis of interviews with parents about their experiences and psychoeducational needs when supporting a young person who engages in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 49 publications
2
47
0
Order By: Relevance
“…Parents experienced ongoing distress and fear, coupled with hypervigilance, anticipatory dread, and a decrease in their own mental health. These results reflect findings from previous research [19,21,[23][24][25]34], reiterating the feelings of distress and fear in parents whose adolescent self-harms and continuing to highlight the unmet needs of this group of parents. The qualitative analysis also contributed to a further understanding of the impact of adolescent self-harm on the wider family and social engagement.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Parents experienced ongoing distress and fear, coupled with hypervigilance, anticipatory dread, and a decrease in their own mental health. These results reflect findings from previous research [19,21,[23][24][25]34], reiterating the feelings of distress and fear in parents whose adolescent self-harms and continuing to highlight the unmet needs of this group of parents. The qualitative analysis also contributed to a further understanding of the impact of adolescent self-harm on the wider family and social engagement.…”
Section: Discussionsupporting
confidence: 87%
“…Secondly, Morgan et al [33] and Ferrey et al [23] reported that parents of adolescents who self-harm frequently endorsed low levels of social support. One recent study has also investigated the experiences and needs of parents and carers of young people who self-harm [34]. It was found that parents express the need for greater support to help them support their child, as well as access to resources that increase their knowledge and understanding of self-harm.…”
Section: Introductionmentioning
confidence: 99%
“…Offering multiple methods may also allow more potential participants to take part in qualitative research as their decision to participate is influenced by their perception of being able to contribute to the study via the given methods [ 33 ]. Based on the literature [ 34 , 35 , 36 ], and our experience in qualitative research [ 10 , 26 , 37 ], we estimated the sample size of adolescents and parents required to answer the research question to be between 15 and 20 participants each.…”
Section: Methodsmentioning
confidence: 99%
“…As the needs of individual carers will differ, such diversity seems to be the most appropriate approach. Carers should also be supported in their ability for self-care and help-seeking, including challenging a belief that taking care of their own needs is selfish (Krysinska et al, 2020).…”
Section: Recommendations For Future Research and Clinical Practicementioning
confidence: 99%